Financial management practices of selected Pantawid Pamilyang Pilipino program families in Barangay Wawa, Nasugbu, Batangas - Delos Reyes, John Edward L. (College of Home Economics, University of the Philippines Diliman, 2014)
This study aims to describe financial management practices of selected Pantawid Pamilyang Pilipino Program (Pantawid Pamilya) recipients, identify the factors related to financial management practices and determine the relationship between these factors and financial management practices of the program recipient households. Snowball sampling was used to select 30 respondents from Barangay Wawa, Nasugbu, Batangas. Data about the individual, family and Pantawid Pamilya factors were gathered through an interview using a researcher-administered questionnaire which includes the Financial Management Behavior Scale. The data were analyzed using descriptive statistics and Pearson?s correlation. Results show that the respondents have good overall financial management practices. In the dimensions of financial management, the respondents were found to have good budgeting, spending and credit management practices; while their saving practices were satisfactory. There is no individual, family and program factor that was found to have a significant relationship with the overall financial management practices of the respondents; but some factors have significant relationships with some dimensions of financial management. Household size and the number of years receiving Pantawid Pamilya grants were found to have positive significant relationships with the respondents? saving practices. Total additional income and the estimated monthly expenses were found to have negative relationships with credit management practices of the respondents.